ANALISIS PERILAKU MASYARAKAT DALAM UPAYA MENCIPTAKAN KEBERSIHAN LINGKUNGAN DI KOTA PEKANBARU (STUDI KASUS KELURAHAN SIMPANG BARU) - ", Nazaruddin; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In response to environmental cleanliness in accordance with local regulations digulirkannyaNo. pekanbaru city. 08 Year 2008 on K3 (Health, Beauty, Order) and of Simpang VillageNew Vision mission in environmental hygiene. Village communities still lack experience andpengatahuan about the cleanliness of the environment, especially on trash. People stilllittering the place, not in accordance with the principle of local regulations pekanbaru cityNo. 08 of 2008 on K3 (Health, Beauty, Order) This study aims to know the how people'sbehavior in order to create environmental hygiene in urban intersections as well as knowingthe new factors that influence people's behavior in creating a clean environment in thevillage new intersection. This study used a descriptive qualitative data collection techniquesby observation and informant interviews were obtained from studies that have beendetermined by purposive sampling technique. Where the behavior can be seen from:environment, culture, social class and other group membership, this can be seen with earlierin creating public awareness of environmental cleanliness.There are still a lot of peoplelittering the place, In this study the factors known to affect people's behavior in order tocreate environmental hygiene in urban new intersections are: Environment Society, SocietyExecutive attitude.Keywords: Behavior, Environment Society, Culture.